Effectiveness, safety, and cost–utility of a knee brace in medial knee osteoarthritis: the ERGONOMIE randomized controlled trial. Issue 4 (April 2021) - Gueugnon, M.; Fournel, I.; Soilly, A.-L.; Diaz, A.; Baulot, E.; Bussière, C.; Casillas, J.M.; Cherasse, A.; Conrozier, T.; Loeuille, D.; Maillefert, J.-F.; Mazalovic, K.; et al.
Summary: Objective: This pragmatic, multicenter, open-label, randomized controlled trial (RCT) aimed to compare the effectiveness, safety, and cost–utility of a custom-made knee brace versus usual care over 1 year in medial knee osteoarthritis (OA). Design: 120 patients with medial knee OA (VAS pain at rest >40/100), classified as Kellgren–Lawrence grade II-IV, were randomized into two groups: ODRA plus usual care (ODRA group) and usual care alone (UCA group). The primary effectiveness outcome was the change in VAS pain between M0 and M12. Secondary outcomes included changes over 1 year in KOOS (function) and OAKHQOL (quality of life) scores. Drug consumption, compliance, safety of the knee brace, and cost–utility over 1 year were also assessed. Results: The ODRA group was associated with a higher improvement in: VAS pain (adjusted mean difference of −11.8; 95% CI: −21.1 to −2.5); all KOOS subscales (pain: +8.8; 95% CI: 1.4–16.2); other symptoms (+10.4; 95% CI: 2.7–18); function in activities of daily living (+9.2; 95% CI: 1.1–17.2); function in sports and leisure (+12.3; 95% CI: 4.3–20.3); quality of life (+9.9; 95% CI: 0.9–15.9), OAKHQOL subscales (pain: +14.8; 95% CI: 5.0–24.6); and physical activities (+8.2; 95% CI: 0.6–15.8), and with a significant decrease in analgesics consumption at M12 compared with the UCA group. Despite localized side-effects, observance was good at M12 (median: 5.3 h/day). The ODRA group had a more than 85% chance of being cost-effective for a willingness-to-pay threshold of €45 000 per QALY. Conclusions: The ERGONOMIE RCT demonstrated significant clinical benefits of an unloader custom-made knee brace in terms of improvements in pain, function, and some aspects of quality of life over 1 year in medial knee OA, as well as its potential cost–utility from a societal perspective.